2004
DOI: 10.1194/jlr.r300016-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 in the central nervous system

Abstract: Phospholipase A 2 (PLA 2 ) belongs to a family of enzymes that catalyze the cleavage of fatty acids from the sn-2 position of phospholipids. There are more than 19 different isoforms of PLA 2 in the mammalian system, but recent studies have focused on three major groups, namely, the group IV cytosolic PLA 2 , the group II secretory PLA 2 (sPLA 2 ), and the group VI Ca 2 ؉ -independent PLA 2 . These PLA 2 s are involved in a complex network of signaling pathways that link receptor agonists, oxidative agents, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
91
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(104 citation statements)
references
References 115 publications
10
91
0
3
Order By: Relevance
“…iPLA 2 involvement in oxidant-induced phospholipid hydrolysis has also been recognized to occur in uterine stromal cells (21) and, more recently, in astrocytes as well (43). Interestingly, however, in cells such as alveolar macrophages (31) and vascular smooth muscle cells (32), oxidant-induced AA mobilization was found to result from impairment of fatty acid incorporation into phospholipids.…”
Section: Resultsmentioning
confidence: 99%
“…iPLA 2 involvement in oxidant-induced phospholipid hydrolysis has also been recognized to occur in uterine stromal cells (21) and, more recently, in astrocytes as well (43). Interestingly, however, in cells such as alveolar macrophages (31) and vascular smooth muscle cells (32), oxidant-induced AA mobilization was found to result from impairment of fatty acid incorporation into phospholipids.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that PLA 2 s, and iPLA 2 ␥ in particular, play major roles in lipid metabolic pathways vital for normal neuronal function (8,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system, phospholipase A 2 s (PLA 2 s) 3 play critical roles in cellular growth, lipid homeostasis, and second messenger generation (8,9). PLA 2 s catalyze the cleavage of acyl groups from glycerophospholipids, generating free fatty acids and lysophospholipids, thereby initiating dual pathways of signal transduction (10).…”
mentioning
confidence: 99%
“…Phospholipase A 2 (PLA 2 ) is a family of enzymes that hydrolyze the acyl bond of glycerophospholipids at the sn-2 position to produce free fatty acid and lysophospholipids [15][16][17]. The metabolic products of PLA 2 s play important roles in cell death [18].…”
Section: Introductionmentioning
confidence: 99%